Aqueous two-phase systems: Towards novel and more disruptive applications - Pereira, Jorge F.B. [UNESP]; Freire, Mara G.; Coutinho, João A.P. (Elsevier, 2020)
Aqueous two-phase systems (ATPS) have been mainly proposed as powerful platforms for the separation and purification of high-value biomolecules. However, after more than seven decades of research, ATPS are still a major academic curiosity, without their wide acceptance and implementation by industry, leading to the question whether ATPS should be mainly considered in downstream bioprocessing. Recently, due to their versatility and expansion of the Biotechnology and Material Science fields, these systems have been investigated in novel applications, such as in cellular micropatterning and bioprinting, microencapsulation, to mimic cells conditions, among others. This perspective aims to be a reflection on the current status of ATPS as separation platforms, while overviewing their applications, strengths and limitations. Novel applications, advantages and bottlenecks of ATPS are further discussed, indicating some directions on their use to create innovative industrial processes and commercial products.
Keywords: Aqueous biphasic systems; Aqueous two-phase systems; Bioanalytics; Biomaterials; Bioprinting; Biotechnology; Micropatterning; Purification; Separation